Religion and Nurses' Attitudes To Euthanasia and Physician Assisted Suicide - Gielen, Joris (Nursing ethics, 2009)
In this review of empirical studies we aimed to assess the influence of religion and world view on nurses' attitudes towards euthanasia and physician assisted suicide. We searched PubMed for articles published before August 2008 using combinations of search terms. Most identified studies showed a clear relationship between religion or world view and nurses' attitudes towards euthanasia or physician assisted suicide. Differences in attitude were found to be influenced by religious or ideological affiliation, observance of religious practices, religious doctrines, and personal importance attributed to religion or world view. Nevertheless, a coherent comparative interpretation of the results of the identified studies was difficult. We concluded that no study has so far exhaustively investigated the relationship between religion or world view and nurses' attitudes towards euthanasia or physician assisted suicide and that further research is required.